On The Trends and Periodicities of Rainfall in Some Districts of East Rajasthan - Ramasastri, K S; Jain, Vibha (Annals of Arid Zone, 2016)
Since 1979 onwards many districts in east Rajasthan have been experiencing deficit rainfall year after year. To understand the phenomenon of below normal rainfall for more than two years in succession in many districts, a statistical study of rainfall data from seven contiguous districts in cast Rajasthan was undertaken. Besides tests for randomness, trend analysis by linear and polynomial regression were attempted. Rainfall in the non-monsoon season did not have any relationship with preceding monsoon season rainfall. The serial correlation (nearly zero) indicated no persistence There was no curvilinear trend although some stations in each of the cistricts showed some linear trend.